2019
DOI: 10.1097/md.0000000000018478
|View full text |Cite
|
Sign up to set email alerts
|

Description of a transient proximal tubulopathy induced by amino acids perfusion in peptide receptor radionuclide therapy

Abstract: Rationale: Peptide receptor radionuclide therapy (PRRT) with radiolabeled somatostatin analogs is a targeted internal radiotherapy method used to treat tumors expressing somatostatin receptors. Concomitant amino acids perfusion is systematically performed in order to inhibit the proximal tubular uptake of the radionuclide and thus prevent nephrotoxicity.Patient concerns: a 67-year-old woman with an intestinal neuroendocrine tumor with multiple lymphadenopathies and liver metastases. The patient displayed a car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…To reduce the risk of renal toxicity after administration of [177Lu]Lu-SSRT, protocols for renal protection have been developed involving co-infusion of amino acids that compete for the megalin receptor on tubular cells. Immediate and reversible side effects following therapy, like vomiting and cramps, are ascribed to renal-protection protocols rather than radiation exposure [ 52 , 53 ]. For [177Lu]Lu-SSRT, including concurrent kidney protection, the level of reported nephrotoxicity is limited to disease-related events, and for therapy with [177Lu]Lu-PSMA, it appears to be negligible at current activities [ 28 , 54 ].…”
Section: Radiobiological Effects On Normal Tissues and Tumoursmentioning
confidence: 99%
“…To reduce the risk of renal toxicity after administration of [177Lu]Lu-SSRT, protocols for renal protection have been developed involving co-infusion of amino acids that compete for the megalin receptor on tubular cells. Immediate and reversible side effects following therapy, like vomiting and cramps, are ascribed to renal-protection protocols rather than radiation exposure [ 52 , 53 ]. For [177Lu]Lu-SSRT, including concurrent kidney protection, the level of reported nephrotoxicity is limited to disease-related events, and for therapy with [177Lu]Lu-PSMA, it appears to be negligible at current activities [ 28 , 54 ].…”
Section: Radiobiological Effects On Normal Tissues and Tumoursmentioning
confidence: 99%
“…However, it has also been shown that yttrium-90-labeled peptides had a higher chance of inducing high-grade renal toxicity compared to lutetium-177-labeled peptides, especially in patients with risk factors relevant for creatinine clearance loss [ 31 , 32 ]. Nevertheless, to limit renal toxicity, a cocktail of lysine and arginine can be administered to patients after which potential toxicity can be monitored, increasing the safety of the radiopeptide [ 33 - 34 ]. So far, maybe more promising is the combination of yttrium-90 and lutetium-177 for the treatment of NETs.…”
Section: Improving Peptide Receptor Radionuclide Therapymentioning
confidence: 99%